DIGITAL RELIGIOUS LITERACY: COUNTERING RADICALISM AMONG INDONESIA'S YOUNG GENERATION - Prasetia, Senata Adi (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2025)
This article examines the role of digital religious literacy in countering radicalism, focusing on tafsiralquran.id, an online platform that offers accessible, reliable, and contextualized interpretations of the Qur'an. Radicalism among Indonesia’s young generation has become a pressing concern, with digital platforms increasingly serving as both a medium for radical ideologies and a space for counter-narratives. Employing a qualitative case study, the research integrates content analysis and observational studies to assess how tafsiralquran.id promotes critical thinking, religious moderation, and resilience against extremist ideologies. Drawing on Gary Bunt’s Cyber-Islamic Environments framework, the study positions tafsiralquran.id as a model of localized, grassroots efforts in fostering pluralistic and moderate Islamic perspectives in the digital realm. The findings reveal that tafsiralquran.id bridges traditional Islamic scholarship with digital spaces, providing youth with credible sources and contextual understandings of Islamic teachings. This enhances their ability to critically evaluate and reject radical narratives. This article highlights the importance of integrating digital religious literacy into counter-radicalization strategies, emphasizing the potential of platforms like tafsiralquran.id to build an informed and resilient digital community. Recommendations are provided for expanding such initiatives to further strengthen their impact on religious moderation and counter-radicalism in Indonesia and beyond.